Compression of morbidity in a progeroid mouse model through the attenuation of myostatin/activin signalling. Issue 3 (27th March 2019) - Alyodawi, Khalid; Vermeij, Wilbert P.; Omairi, Saleh; Kretz, Oliver; Hopkinson, Mark; Solagna, Francesca; Joch, Barbara; Brandt, Renata M.C.; Barnhoorn, Sander; van Vliet, Nicole; Ridwan, Yanto; Essers, Jeroen; et al.
Abstract: Background: One of the principles underpinning our understanding of ageing is that DNA damage induces a stress response that shifts cellular resources from growth towards maintenance. A contrasting and seemingly irreconcilable view is that prompting growth of, for example, skeletal muscle confers systemic benefit. Methods: To investigate the robustness of these axioms, we induced muscle growth in a murine progeroid model through the use of activin receptor IIB ligand trap that dampens myostatin/activin signalling. Progeric mice were then investigated for neurological and muscle function as well as cellular profiling of the muscle, kidney, liver, and bone. Results: We show that muscle of Ercc1 Δ/− progeroid mice undergoes severe wasting (decreases in hind limb muscle mass of 40–60% compared with normal mass), which is largely protected by attenuating myostatin/activin signalling using soluble activin receptor type IIB (sActRIIB) (increase of 30–62% compared with untreated progeric). sActRIIB‐treated progeroid mice maintained muscle activity (distance travel per hour: 5.6 m in untreated mice vs. 13.7 m in treated) and increased specific force (19.3 mN/mg in untreated vs. 24.0 mN/mg in treated). sActRIIb treatment of progeroid mice also improved satellite cell function especially their ability to proliferate on their native substrate (2.5 cells per fibre in untreated progeroids vs. 5.4 in sActRIIB‐treated progeroids after 72 h in culture). Besides direct protective effects on muscle, we show systemic improvements to other organs including the structure and function of the kidneys; there was a major decrease in the protein content in urine (albumin/creatinine of 4.9 sActRIIB treated vs. 15.7 in untreated), which is likely to be a result in the normalization of podocyte foot processes, which constitute the filtration apparatus (glomerular basement membrane thickness reduced from 224 to 177 nm following sActRIIB treatment). Treatment of the progeric mice with the activin ligand trap protected against the development of liver abnormalities including polyploidy (18.3% untreated vs. 8.1% treated) and osteoporosis (trabecular bone volume; 0.30 mm 3 in treated progeroid mice vs. 0.14 mm 3 in untreated mice, cortical bone volume; 0.30 mm 3 in treated progeroid mice vs. 0.22 mm 3 in untreated mice). The onset of neurological abnormalities was delayed (by ~5 weeks) and their severity reduced, overall sustaining health without affecting lifespan. Conclusions: This study questions the notion that tissue growth and maintaining tissue function during ageing are incompatible mechanisms. It highlights the need for future investigations to assess the potential of therapies based on myostatin/activin blockade to compress morbidity and promote healthy ageing.